The Effect of Brand Trust and Brand Equity on Telkomsel Card Brand Loyalty (Case Study on Telkomsel Card Users on Customers in the Barombong Area) - Aulia Aulia; Sherry Adelia Natsir Kalla; Indriana Indriana; Ichlazul Ghifary (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine and analyze the effect of brand trust and brand equity on Telkomsel card brand loyalty (a case study on Telkomsel card users in customers in the Barombong area. The data collection technique used in this study is survey technique by distributing questionnaires and studies). documentation. The population and sample used in this study were 100 respondents. The data analysis technique used was multiple linear regression analysis which was processed using SPSS version 28 software. The results of the study show that based on the t-test that has been carried out on the brand trust variable (X1) on brand loyalty (Y), the value of tcount ttable or 2,585 1.660, with a significant value is 0.011 0.05. Based on the results of the t-test of the brand equity variable (X2) on brand loyalty (Y), the value of tcount ttable or 2.173 1.660, with a significant value is 0.032 0.05. The conclusion of this study shows that the variables of brand trust and brand equity have a positive and significant effect on Telkomsel card brand loyalty to customers in the Barombong area.